Drosophila Me31B is a Dual eIF4E-Interacting Protein. Issue 5 (1st March 2023) - Layana, Carla; Vilardo, Emiliano Salvador; Corujo, Gonzalo; Hernández, Greco; Rivera-Pomar, Rolando
Graphical abstract: Highlights: Me31B might be involved in mRNPs repression by interaction with specific eIF4E isoforms. Drosophila eIF4E-1 and eIF4E-3 occur in PBs and interact with the DEAD-box RNA helicase Me31B. Me31B is a novel type of eIF4E-interacting protein with specific interaction domains for eIF4E-1 and eIF4E-3 isoforms. Abstract: Eukaryotic translation initiation factor 4E (eIF4E) is a key factor involved in different aspects of mRNA metabolism. Drosophila melanogaster genome encodes eight eIF4E isoforms, and the canonical isoform eIF4E-1 is a ubiquitous protein that plays a key role in mRNA translation. eIF4E-3 is specifically expressed in testis and controls translation during spermatogenesis. In eukaryotic cells, translational control and mRNA decay is highly regulated in different cytoplasmic ribonucleoprotein foci, which include the processing bodies (PBs). In this study, we show that Drosophila eIF4E-1 and eIF4E-3 occur in PBs along the DEAD-box RNA helicase Me31B. We show that Me31B interacts with eIF4E-1 and eIF4E-3 by means of yeast two-hybrid system, FRET in D. melanogaster S2 cells and coimmunoprecipitation in testis. Truncation and point mutations of Me31B proteins show two eIF4E-binding sites located in different protein domains. Residues Y401-L407 (at the carboxy-terminus) are essential for interaction with eIF4E-1, whereas residues F63-L70 (at the amino-terminus) are critical for interaction with eIF4E-3. The residue W117 in eIF4E-1 and the homolog position F103 in eIF4E-3 are necessary for Me31B-eIF4E interaction suggesting that the change of tryptophan to phenylalanine provides specificity. Me31B represents a novel type of eIF4E-interacting protein with dual and specific interaction domains that might be recognized by different eIF4E isoforms in different tissues, adding complexity to the control of gene expression in eukaryotes.